"On-off"controlled H2 evolution and O2 evolution upon NH3BH3 hydrolysis resp·H2O2 decomposition on Pt/ZIF-67. (1st June 2023) - Rong, Qi; Huang, Wenkai; Xu, Fuhua; Wang, Yanlan; Wang, Changlong; Liu, Xiang
Graphical abstract: Highlights: Pt/ZIF-67 was synthesized by the immobilization of ultrafine PtNPs at the surface of ZIF-67. Pt/ZIF-67 shown superior catalytic activity in both H2 and O2 evolution. The "on–off" switch for H2 evolution from NH3 BH3 hydrolysis was developed. NH3 BH3 and H2 O2 are deemed as an economic and safe H2 resp. O2 carrier for fuel cell. Abstract: In spite of significant developments are accomplished in the exploration of H2 and O2 evolution upon water electrolysis/photolysis, this remains a challenge to design and develop ideal catalytic systems for this reaction and to isolate H2 from H2 -O2 mixture with membranes. Herein, a series of ZIF-67-supported transition metal nanoparticles (TMNPs/ZIF-67), including Pt, Ir, Pd, Rh, Au and Ag, via immobilization of ultrafine TMNPs at the surface of ZIF-67, have been designed and developed for the selective H2 generation from NH3 BH3 hydrolysis and O2 evolution upon H2 O2 decomposition. In particular, the optimized nanocatalyst Pt/ZIF-67 presents the super-high catalytic property in the both H2 evolution upon NH3 BH3 hydrolysis (689 mol(H2 )·molPt -1 ·min −1 ) and O2 evolution upon H2 O2 decomposition (979 mol(O2 )·molPt -1 ·min −1) at 30 °C. Importantly, the selective "on–off" control for demand-based H2 generation from NH3 BH3 hydrolysis was successfully realized by Zn 2+ /EDTA-2Na system. This highly efficient Pt/ZIF-67 proposed a new method for the promising potential application of ammonia borane and hydrogen peroxide as an economic and safe H2 resp. O2 carrier for fuel cell.